A Modified Inertial Shrinking Projection Method for Solving Inclusion Problems and Split Equilibrium Problems in Hilbert Spaces - Cholamjiak, Watcharaporn; Khan, Suhel Ahmad; Suantai, Suthep (Communications in Mathematics and Applications, 2019)
In this paper, we propose a modified inertial forward-backward splitting method for solving the split equilibrium problem and the inclusion problem. Then we establish the weak convergence theorem of the proposed method. Using the shrinking projection method, we obtain strong convergence theorem. Moreover, we provide some numerical experiments to show the efficiency and the comparison.
Keywords: Inertial method; Inclusion problem; SP-iteration; Forward-backward algorithm; Split equilibrium problem